Discordance of the PAM50 Intrinsic Subtypes Compared with Immunohistochemistry-Based Surrogate in Breast Cancer Patients: Potential Implication of Genomic Alterations of Discordance - Kim, Hee Kyung; Park, Kyung Hee; Kim, Youjin; Park, Song Ee; Lee, Han Sang; Lim, Sung Won; Cho, Jang Ho; Kim, Ji-Yeon; Lee, Jeong Eon; Ahn, Jin Seok; Im, Young-Hyuck; Yu, Jong Han; et al. (Cancer research and treatment, 2019)
We aimed to analyze the discordance between immunohistochemistry (IHC)-based surrogate subtyping and PAM50 intrinsic subtypes and to assess overall survival (OS) according to discordance. A total of 607 patients were analyzed. Hormone receptor (HR) expression was evaluated by IHC, and human epidermal growth factor receptor 2 (HER2) expression was analyzed by IHC and/or fluorescence in situ hybridization. PAM50 intrinsic subtypes were determined according to 50 cancer genes using the NanoString nCounter Analysis System. We matched concordant tumor as luminal A and HR+/HER2-, luminal B and HR+/HER2+, HR-/HER2+ and HER2-enriched, and triple-negative breast cancer (TNBC) and normal- or basal-like. We used Ion Ampliseq Cancer Panel v2 was used to identify the genomic alteration related with discordance. The Kaplan-Meier method was used to estimate OS. In total, 233 patients (38.4%) were discordant between IHC-based subtype and PAM50 intrinsic subtype. Using targeted sequencing, we detected somatic mutation-related discordant breast cancer including the VHL gene in the HR+/HER2- group (31% in concordant group, 0% in discordant group, p=0.03) and the IDH and RET genes (7% vs. 12%, p=0.02 and 0% vs. 25%, p=0.02, respectively) in the TNBC group. Among the luminal A/B patients with a discordant result had significantly worse OS (median OS, 73.6 months vs. not reached; p < 0.001), and among the patients with HR positivity, the basal-like group as determined by PAM50 showed significantly inferior OS compared to other intrinsic subtypes (5-year OS rate, 92.2% vs. 75.6%; p=0.01). A substantial portion of patients showed discrepancy between IHC subtype and PAM50 intrinsic subtype in our study. The survival analysis demonstrated that current IHC-based classification could mislead the treatment and result in poor outcome. Current guidelines for IHC might be updated accordingly.